Motivación en el proceso de aprendizaje de lengua y literatura de los estudiantes de décimo año de educación básica del Colegio Nacional Nueve de Octubre período lectivo 2010-2011. - Barreiro Ortega, Lady Alexandra (2011)
Motivation is the interest of the students for their own learning or activities that lead to it. Interest may acquire, maintain or increase depending on intrinsic and extrinsic elements. Therefore the research topic is: Motivation in the learning process language and communication students of tenth year of basic education school National Nueve de Octubre school 2009-2010.